2014
DOI: 10.4103/0976-3147.133576
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of depression and type 2 diabetes in Morocco: Economical and social components

Abstract: Background:The global prevalence of diabetes is increasing worldwide. In Morocco, diabetes and depression are major public health problems, requiring improvement in their care. Diabetes and depression are associated with morbidity and early mortality. This association contributes to raising the risk of the complications that occur, while causing higher suffering to patients, as also an increased cost toward healthcare.Aim:This study aims to assess the prevalence of depression in patients with type 2 diabetes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Consistent with previous research findings, 32 49 we found that a lower educational level was associated with a higher depression rate. In developing countries, lower educational level is associated with a lack of social security, 49 poorer understanding and knowledge about the prevention and control of diabetes and an increased likelihood of developing depression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous research findings, 32 49 we found that a lower educational level was associated with a higher depression rate. In developing countries, lower educational level is associated with a lack of social security, 49 poorer understanding and knowledge about the prevention and control of diabetes and an increased likelihood of developing depression.…”
Section: Discussionsupporting
confidence: 92%
“…In developing countries, lower educational level is associated with a lack of social security,49 poorer understanding and knowledge about the prevention and control of diabetes and an increased likelihood of developing depression.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, women had a 1.984-fold higher risk of depression than men. El Mahalli revealed that unmarried patients with diabetes were three times more depressed than married ones [ 26 ]. In our study, unmarried residents had a higher prevalence of depression than married ones, although the difference was not significant (12.6% vs. 8.3%, p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies, such as in [2], have shown that diabetes is one of major public health problems in Morocco, and that it causes early mortality of patients while at the same time increasing healthcare costs (cost of drugs, hospitalizations, biological tests, visits to physicians, etc.) As stated in [3], the direct cost of diabetes in Morocco is estimated to be between US $0.47 and US $1.5 billion whereas the indirect cost is estimated to be around US $2 billion.…”
Section: Introductionmentioning
confidence: 99%